Dynamics of development of industrial parks in Russia - V. V. Kuznetsov (Путеводитель предпринимателя)
The globalization of market conditions leads to the development of positions that influence the modification of the national economy. There is a change in business models, a rearrangement of the system of international division of labor. One of the modern business models is the investment and construction of industrial parks, industrial clusters that integrate on their territory the production and logistics capacities necessary for the optimal production and distribution of certain goods. The development of these models in the country, in addition to optimizing production and logistics processes, also makes it possible to influence the economy of the region in which the park is located, both from an economic and demographic point of view, providing jobs. The study describes the current state of development of industrial parks as one of the main sectors of industrial production.